Analisis Proses Rekrutmen dan Seleksi Terhadap Kinerja Karyawan pada PT PLN (PERSERO) - Nurafni Putri Yulia (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to analyze the recruitment and selection process on employee performance at PT PLN (Persero), one of the largest food and beverage companies in Indonesia. The main focus of the study is to identify the stages of recruitment and selection implemented and evaluate their effectiveness in supporting the fulfillment of competent workforce needs. The method of writing this scientific article is qualitative using the SLR (Systematic Literature Review) approach, namely a literature review study of Human Resource Management through the stages of collecting 15 articles according to the topic, reading and taking notes, and selecting articles according to research objectives, managing research materials and concluding the results. The results of the study indicate that PT PLN (Persero) implements an open and competitive recruitment system, through online media and collaboration with educational institutions. The selection process consists of several stages, starting from administrative screening to in-depth interviews and psychological tests. Although the process is systematic, there are still several obstacles, such as time constraints in mass selection and incompatibility between applicants' backgrounds and available positions. This study suggests that PT PLN (Persero) continue to develop a competency-based selection system and utilize digital technology more optimally to increase process efficiency.